2019
DOI: 10.1007/jhep03(2019)061
|View full text |Cite
|
Sign up to set email alerts
|

Emergent geometry from stochastic dynamics, or Hawking evaporation in M(atrix) theory

Abstract: We develop an microscopic model of the M-theory Schwarzschild black hole using the Banks-Fischler-Shenker-Susskind Matrix formulation of quantum gravity. The underlying dynamics is known to be chaotic, which allows us to use methods from Random Matrix Theory and non-equilibrium statistical mechanics to propose a coarse-grained bottom-up picture of the event horizon -and the associated Hawking evaporation phenomenon. The analysis is possible due to a hierarchy between the various timescales at work. Event horiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…we may not assume that the background is on shell as we have done so. If object 1 were to be a black hole, we expect that the chaotic nature of Matrix theory admits a metastable spherical configuration that is long-lived as it evaporates away slowly via Hawking radiation [4]. It has been shown that this stochastic short timescale dynamics can be effectively modeled by adding by hand a quadratic mass term to the action.…”
Section: Quantum Entanglement and Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…we may not assume that the background is on shell as we have done so. If object 1 were to be a black hole, we expect that the chaotic nature of Matrix theory admits a metastable spherical configuration that is long-lived as it evaporates away slowly via Hawking radiation [4]. It has been shown that this stochastic short timescale dynamics can be effectively modeled by adding by hand a quadratic mass term to the action.…”
Section: Quantum Entanglement and Gravitymentioning
confidence: 99%
“…(49) 4 One can also consider the probe to be a graviton. As a result, α 2 → 0 and we must keep the ε 2 2 term from (38).…”
Section: Quantum Entanglement and Gravitymentioning
confidence: 99%